EVALUATION OF THE IMPLEMENTATION OF INCLUSIVE EDUCATION AT CIKAMPEK SELATAN PUBLIC ELEMENTARY SCHOOL - DWIPUTRA, Yoga; CHAERUNNISA, Connie; RISMITA, Rismita (Journal of Education and Leadership in Education, 2024)
This research aims to evaluate the implementation of inclusive education at SD Negeri Cikampek Selatan 1, Cikampek District, Karawang Regency. A qualitative descriptive approach using the CIPP (Context, Input, Process, Product) evaluation model was employed. Data was collected through interviews, observations, and documentation from teachers, the school principal, and the school committee. The context evaluation shows that the school has the required permission and guidelines for inclusive education, serving children with mild to moderate special needs. The input evaluation reveals inadequate special facilities, modified curriculum, uneven special training, and no special assistant teachers. The process evaluation indicates that teachers' competencies in handling special needs students are good, with individual handling, funding from BOS funds, and no further monitoring from relevant authorities. The product evaluation shows that the academic and non-academic achievements of special needs children are average, with 8 students being served. Based on the findings, the evaluation recommends: 1) Context: Ensure a legal basis, supported by an Inclusive School Implementation Decree; 2) Input: Conduct assessments during student admissions to categorize prospective special needs students; 3) Process: Modify the curriculum to meet the needs of special needs students; 4) Product: Provide additional life skills for special needs students to meet their needs.